L-band scintillation activity and space-time structure of low-latitude UHF scintillations - Bhattacharyya, A.; Groves, K. M.; Basu, S.; Kuenzler, H.; Valladares, C. E.; Sheehan, R. (My University, 2003)
[1] Spatial correlation function of intensity scintillation patterns produced by the propagation of a UHF signal through irregularities in the nighttime low-latitude ionosphere is deduced from an analysis of spaced receiver records of such scintillations. This analysis requires that random temporal variations of the irregularity drift speed be taken into account. It is seen from the results that the occurrence of strong scintillations on an L-band signal requires the presence of short (âˆ¼20 m) coherence scale lengths in the UHF scintillation pattern obtained in the plane of the receiver. This condition is satisfied near the crest of the equatorial ionization anomaly (EIA) region, but not near the dip equator. In the decay phase of L-band scintillations recorded near the crest of the EIA region, the maximum strength of these scintillations at any point in time is found to be correlated with the magnetic eastward drift speed of the pattern of intensity scintillations on an UHF signal recorded in this region, which is determined mainly by the magnetic eastward drift velocity of the ionospheric irregularites. Dependence of the corresponding strength of UHF scintillations on the drift speed indicates that toward the end of the decay phase of L-band scintillations, the irregularity power spectrum steepens, and the large scale irregularities that remain can cause the UHF signal to be focused in the plane of the receiver, yielding UHF S4-indices greater than one, while focusing of the UHF signal is less evident at earlier times when there is focusing of the L-band signal.
Keywords: Equatorial; Ionosphere; Scintillations; UHF scintillations; L-band